2015
DOI: 10.3748/wjg.v21.i3.944
|View full text |Cite
|
Sign up to set email alerts
|

Centralized isolation ofHelicobacter pylorifrom multiple centers and transport condition influences

Abstract: Transportation of specimens within 24 h and below 24 °C is reasonable and acceptable for centralized culture of multicenter H. pylori samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Though selective medium containing antibiotic additives (nalidixic acid, polymyxin B, and bacitracin) was used for H. pylori isolation, non-H. pylori still grew and affected the growth of H. pylori in some cases, and the positive rate of H. pylori isolation was only approximately 30%, which is similar to that reported previously. [52][53][54] To improve the positive rate of isolation, inoculation was performed immediately after sampling or transporting samples at low temperatures, using dry ice to keep them cold, and adding nalidixic and bacitracin along with H. pylori-selective supplements in the medium to avoid the growth of non-H. pylori. This is a small samplesize study, but we did find a general heterogeneity of H. pylori in the stomachs of local patients.…”
Section: Discussionmentioning
confidence: 99%
“…Though selective medium containing antibiotic additives (nalidixic acid, polymyxin B, and bacitracin) was used for H. pylori isolation, non-H. pylori still grew and affected the growth of H. pylori in some cases, and the positive rate of H. pylori isolation was only approximately 30%, which is similar to that reported previously. [52][53][54] To improve the positive rate of isolation, inoculation was performed immediately after sampling or transporting samples at low temperatures, using dry ice to keep them cold, and adding nalidixic and bacitracin along with H. pylori-selective supplements in the medium to avoid the growth of non-H. pylori. This is a small samplesize study, but we did find a general heterogeneity of H. pylori in the stomachs of local patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators suggested that rapid transport of biopsy specimens in an appropriate transport medium at low temperature is essential for a satisfactory recovery of H pylori 3,12 . Others demonstrated that H pylori can survive at room temperature for 24 hours without loss of the viability, indicating that low temperature is not essential for the survival of H pylori 13,14 . Most importantly, rapid transport and specialized transport media had been considered important for high diagnostic yield 12,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Others demonstrated that H pylori can survive at room temperature for 24 hours without loss of the viability, indicating that low temperature is not essential for the survival of H pylori 13,14 . Most importantly, rapid transport and specialized transport media had been considered important for high diagnostic yield 12,14 . Several transport media have been studied, including Stuart's media, urea‐containing saline, and normal saline 12,13,15‐17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dental plaques were broken and cultivated on Columbia agar plates (Oxoid of Thermo Fisher Scientific Inc., Waltham, MA, United States). The rapid urease test (RUT), a commercially available rapid gastric urease test kit, was used to for detecting HP, and the detailed methods of culture and polymerase chain reaction (PCR) are described elsewhere [ 24 , 29 , 30 ]. The sample was identified as positive HP if the test gel color changed from yellow to red within 20 min, up to a maximum of 60 min [ 24 ].…”
Section: Methodsmentioning
confidence: 99%